2022
DOI: 10.1002/wsb.1256
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐metric movement model for identifying elk parturition events

Abstract: For wildlife managers, identifying the time and location of ungulate parturition events is necessary to protect parturition habitat and inform population models. Current methods for identifying parturition events include neonatal capture and monitoring and visual analysis of location data, which are resource intensive and subject to biases. Recently, movement‐based analyses using the spatial and temporal patterns contained in location data have shown promise for identifying parturition behavior; however, quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Due to these behavioral differences, methods developed for specific ungulates may not be as effective when transferring across species and some modification may be required [25,32,33]. Furthermore, methods using multiple movement metrics may be more effective than those using a single metric [34][35][36].…”
Section: Petersonmentioning
confidence: 99%
“…Due to these behavioral differences, methods developed for specific ungulates may not be as effective when transferring across species and some modification may be required [25,32,33]. Furthermore, methods using multiple movement metrics may be more effective than those using a single metric [34][35][36].…”
Section: Petersonmentioning
confidence: 99%
“…Patterns in movement data thus offer a cost‐effective means for identifying parturition in radio‐collared ungulates (DeMars et al, 2013; Nicholson et al, 2019; Peterson et al, 2018). Although multiple methods have been used to infer parturition events, many are sensitive to parameter choices or involve visual observation of movement metrics, which can be time‐intensive (Dettki & Ericsson, 2008; Mohr et al, 2022).…”
Section: Example Applicationsmentioning
confidence: 99%
“…Patterns in movement data thus offer a cost-effective means for identifying parturition in radio-collared ungulates(DeMars et al, 2013;Nicholson et al, 2019;Peterson et al, 2018). Although multiple methods have been used to infer parturition events, many are sensitive to parameter choices or involve visual observation of movement metrics, which can be time-intensive(Dettki & Ericsson, 2008;Mohr et al, 2022).To demonstrate remote identification of parturition, we provide an example of quantifying movements of a pregnant moose (Figure2).Severud et al (2015) confirmed the parturition period by locating the twin calves shortly after their birth. In this case, the first segment is modelled with an intercept and slope of zero, representing typical moose movement, and the second segment is modelled with a change in the mean displacement (i.e.…”
mentioning
confidence: 99%